2003
DOI: 10.2337/diacare.26.10.2741
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Fetal Growth and Body Composition in Women With Different Degrees of Normal Glucose Metabolism

Abstract: OBJECTIVE -To investigate the maternal demographic and metabolic factors contributing to the growth of fetal lean and fat body mass in women whose degree of glucose intolerance is less than that defining gestational diabetes in comparison with women with normal glucose metabolism.RESEARCH DESIGN AND METHODS -Longitudinal sonographic examinations of 66 singleton fetuses without anomalies of nonobese mothers with abnormal oral glucose challenge test (GCT) results and without gestational diabetes (group 1) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Conversely, when glucose availability increases, the rate of release decreases which upregulates IGFs and downregulates IGFbinding proteins in the foetal compartment resulting in an increased foetal growth rate. As a result, we assume that the rate of kcal ingested by the foetus is an increasing function of placental volume, total maternal kcal ingested and the glycaemic index of the maternal diet ( Fraser et al 1988;Clapp 1998Clapp , 2002Parretti et al 2003;Scholl et al 2004;Moses et al 2006). (iv) The pregnancy is considered normal and the foetus is not deprived of energy required to grow.…”
Section: The Foetal Energy Balance Modelmentioning
confidence: 99%
“…Conversely, when glucose availability increases, the rate of release decreases which upregulates IGFs and downregulates IGFbinding proteins in the foetal compartment resulting in an increased foetal growth rate. As a result, we assume that the rate of kcal ingested by the foetus is an increasing function of placental volume, total maternal kcal ingested and the glycaemic index of the maternal diet ( Fraser et al 1988;Clapp 1998Clapp , 2002Parretti et al 2003;Scholl et al 2004;Moses et al 2006). (iv) The pregnancy is considered normal and the foetus is not deprived of energy required to grow.…”
Section: The Foetal Energy Balance Modelmentioning
confidence: 99%
“…22 Many studies have used these findings and applied them to measurements obtained during fetal sonography. [23][24][25][26] Results of these studies indicate that fetal fat, and in particular the truncal fat layer, has a stronger correlation with maternal glycemic control than does estimation of birth weight.…”
Section: Fetal Body Compositionmentioning
confidence: 99%
“…Some investigations have demonstrated that also the MDGI is a signiWcant risk factor for fetal growth and its attendant problems (Kaufmann et al 1992;Berkus and Langer 1993;Moses and Calvert 1995;Thomas et al 2002;Parretti et al 2003).…”
Section: Introductionmentioning
confidence: 98%